Equestrianism: serious leisure and intersubjectivity - Butler, Erin, author; Cross, Jennifer, advisor; Peek, Lori A., committee member; Granger, Ben, committee member (Colorado State University. Libraries, 2010)
Using the concepts of serious leisure and symbolic interactionism, this thesis explores the experiences of equestrians in the hunter/jumper discipline. This thesis draws from ethnographic research methods that utilize a combination of two years of participant observation and in-depth interviews. This research challenges the basis for Mead's (and others') exclusion of nonhuman animals from consideration as "authentic" social actors by highlighting the ways horse owners, in this study, describe their horses as minded, thoughtful individuals. These owners refute the notions that horses are mindless objects or are indistinct from other insensate elements of "nature," (i.e. air, water, or land). Focusing on the interactions between humans and horses, I examine the criteria used by horse owners to define their horses as minded individuals with whom they construct and maintain meaningful and satisfying social relationships. Using the rich and detailed descriptions of participants, I argue that two features of hunter/jumper equestrianism warrant reclassifying it as an amateur pursuit, rather than hobbyist activity: the visible and influential presence of professionals within the sport and owners' perception of horses' subjectivity, which makes the achievement of intersubjectivity possible. I emphasized the role of actions and argue that the concepts of 'mind,' 'self,' and 'personhood' are social constructions that arise from interaction. Furthermore, using the Serious Leisure Perspective as a theoretical foundation I explore key features of hunter/jumper equestrianism beyond merely human-animal 'attachments' or 'bonds.' This thesis considers hunter/jumper equestrianism in terms of serious leisure's six definitional social-psychological elements and confirms the viability of classifying hunter/jumper equestrianism as a form of serious leisure pursuit. Additionally, I present a new model for classifying the negative consequences, or costs, of serious leisure pursuits. Examining hunter/jumper equestrianism as a form of serious leisure highlights the 'serious' costs of participation in a pursuit, which is marginal to both human-animal interaction and leisure activities. Finally, this thesis highlights the potential of studying humans' relationships with horses for advancing an understanding of how personhood, mind, and identity are socially constructed, and the possibility of studying serious leisure pursuits as alternative sites for community, belonging, and identity in an increasingly fragmented post-modern society.
Keywords: serious leisure costs; serious leisure; intersubjectivity; humans and horses; human-animal interaction; animal subjectivity; Horsemanship; Intersubjectivity; Human-animal relationships